Biomechanics of transverse axis of medial longitudinal arch of children's foot based on 3D scanning - Liu, Qinglin; Zhao, Chen; Yang, Xiaoxuan; Tang, Jing; Chen, Jing; Tang, Li; Wu, Jun (Frontiers in Pediatrics, 2023)
Objective To explore the application value of 3D scanning to obtain the parameters of transverse axis of medial longitudinal arch of foot in the biomechanical evaluation of transverse axis of medial longitudinal arch of foot in children. Method The feet of children with flat foot, normal foot and high arched foot were scanned with the Foot Secret 3D scanner in the sitting and standing positions. The scanning data were imported into CATIA v5 software for measurement, to obtain four parameters of transverse axis of medial longitudinal arch from transverse arch angle, external transverse arch angle, curvature and transverse arch cross-sectional area. Result There were statistically significant difference in transverse arch angle, external transverse arch angle and cross-sectional area between sitting and standing positions (p < 0.05). There were statistically significant differences in transverse arch angle, external transverse arch angle, curvature and transverse arch cross-sectional area among children with flat foot, normal foot and high arch foot (p < 0.05). Conclusion The four parameters of transverse arch angle, external transverse arch angle, maximum curvature and cross-sectional area obtained by three-dimensional scanning can detect the changes of transverse axis of children's foot arch in different body positions with different foot types, which can be effectively used for the biomechanical evaluation of transverse axis of children's foot arch.